The Growth and Yield of The Radishes (Raphanus Sativus L.) to doses of nitrogen fertilizer and Potassium fertilizer - Muhammad Syauqi; Tri Handoyo (Jember University Press, 2022)
The Radish (rhaphanus sativus l.) is a horticultural plant that enters into the bulbous bulbous variety. Radishproductivity has always decreased by 2.16%, although in 2016 its productivity increased by 0.11% but it was still lower inproduction (Agricultural Statistics Center, 2017). The low production of turnips is caused by highlanders and few problemsof fertilizing them. One attempt to improve the production of focused turnips on growing them at higher altitudes byexpanding areas where turnips are grown in lowland. A lowland area utilization effort to cultivate turnips by addingnitrogenous macro nutrients and potassium. Nitrogen plays a role as a chlorophyil compiler that is highly responsible for thephotosynthesis of plants and photosynthesizers secreted (Pahlevi, et. 2016). Potassium fertilizers themselves play a vital rolein sustaining turnips, durability of drought and disease pests. Aside from cultivating the use of varieties is something to takenote of in raising turnips. Superior varieties can provide the maximum yield by the growth of good plants. The experimentaims to identify the interaction of nitrogen and potassium fertilizer against the growth and horseradish yields (raphanussativus l.) The giving of the dose of nitrogen fertilizer used is N0 = 0 gr, N2 = 0.8 gr, N3 = 1 gr and potassium fertilizer doseis K0 = 0 gr, K1 = 0.2 gr, K2 = 0.4 gr, K3 = 0.6 gr. Data obtained subsequently was analyzed and tested using DuncanDMRT surplus 5%. Studies indicate that the best combination of treatment was that of a dose of n3 fertilizer treatment = 1 gr,and potassium k3 = 0,6 gr